Tujuh Elemen Dasar Pemerintahan Daerah Sebagai Konsekwensi Strategis Teori Desentralisasi - Hamim, Sofyan Safari (Jurnal Wahana Bina Pemerintahan, 2016)
In theoretical way tehere are generic basic elements in local government institution, in order to implement its autonomy with the best way, as instrument which create democratization process and build welfare in local level, it should pay attention to democracy principle, equalization, equilty, and uniqueness in every region at the Unitary State of the Republic of Indonesia system. The efficiency and effectiveness on implementation of local goverment need to be increased with pay attention more to the correlation aspects between central government and local government and between many regions, potency and the regional differences, also chances and challenges in global competition on unitary system of state goverment implemetation. There at least seven (7) basic elements that build local goverment as strategic consequeces of theory of decentralizaion, they are (1)Governmental Affairs; (2) Instituional; (3) Personal; (4) Local Finance, (5) Regional Representative; (6) Public Service (7)Guidance and Control, that have three dimensions which are philosophical dimension, theoretical dimension, and practical dimension. the basic elements of local government, decentralizaion